(untitled) (World Bulletin of Management and Law, 2025)
This article analyzes the establishment of the Constitutional Oversight Committee, the procedure for its formation, and the legal foundations of its activities. As a key body ensuring the supremacy of the Constitution, the composition of the Committee, the mechanism for appointing and dismissing its members, as well as their powers, are examined. Special attention is given to the principles of impartiality, independence, and legality that underpin the Committee’s operations. The research also includes a comparative analysis of international practices and provides conclusions and recommendations regarding the effectiveness of the current system in Uzbekistan